Perception of the public towards Safe City: A case study at Taman Kenanga Seksyen 1 / Khairun Nisak Farid Waradi and Nabilah Zakariah - Farid Waradi, Khairun Nisak; Zakariah, Nabilah (Faculty of Administrative Science and Policy Studies, 2013)
A safe city can be perceived as a sustainable city, where community can live in more inclusive and secure environment. The security, environment and facilities are important factors that can influence the public perceptions towards safe city. Security is a very vital aspect of life because it ensures that public can feel safe, harmonious and comfortable to live at housing area especially for women and children. In addition, facilities provided also important to prevent the crime incidence frequently occur at housing area. In this research, this study was conducted to determine the public perceptions towards Safe City at Taman Kenanga Seksyen 1, Tengkera Melaka. A sample of 169 residents was involved in this study. The main objectives of this study is to determine the contributing factor that lead the public perceptions towards safe city whether it influenced by security, environmental and facilities factor. The statistic techniques used in this study are Descriptive Statistics, Reliability Analysis, Normality Test, Regression Analysis and Pearson Correlation. This study revealed that the most contributing factor that leads to public perceptions towards safe city is environment. Therefore, this study also can enhance the safety situation and public awareness on crime incidence and to conserve the environments at housing area in order to provide better living place for community.